Crop rotations increased soil ecosystem multifunctionality by improving keystone taxa and soil properties in potatoes - Li, Qing-mei; Zhang, Dai; Zhang, Ji-zong; Zhou, Zhi-jun; Pan, Yang; Yang, Zhi-hui; Zhu, Jie-hua; Liu, Yu-hua; Zhang, Li-feng (Frontiers in Microbiology, 2023)
Continuous cropping of potatoes leads to soil degradation, ecosystem multifunctionality reduction and potato production decline, and these impacts could get to remission through rotation cropping. Although crop rotation promotes soil nutrient, microbial community, and potato yield, its effects on the soil ecosystem multifunctionality, keystone taxa, and the main drivers remain unclear. In the present research, we comparatively explored the affects of potato continuous cropping (PP) and rotation cropping (potato and oat rotation (PO) and potato and forage maize rotation (PFM)) on the soil ecosystem multifunctionality (EMF) as well as the roles of keystone taxa, microbes abundance, chemistry properties in ecosystem multifunctionality improvement. It was demonstrated that soil ecosystem multifunctionality increased in rotation cropping (PO and PFM) over PP. Soil pH was higher in rotation cropping (PO and PFM) compared with PP, while total phosphorus (TP), available phosphorus (AP) were decreased significantly than that in PP. The compositions of bacterial and fungal community markedly altered by crop rotations. Rotation cropping (PO and PFM) improved the beneficial fungi e.g. Schizothecium and Chaetomium, while reduced the abundances of the pathogenic fungi e.g. Altemaria, Fusarium, Verticillium dahiae, Gibberella, Plectosphaerella, Colletotrichum, Phoma, and Lectera compared with PP. Also, co-occurrence patterns for bacterial and fungal were apparently impacted by crop rotations, and keystone taxa e.g., Nitrospira.1, Lysinibacillus, Microlunatus.1, Sphingomonas.3, Bryobacter.1 and Micromonospora, Schizotheciumwere enriched in PO and PFM compared with PP. Structural equation model (SEM) further indicated that cropping systems affected soil ecosystem multifunctionality by mediating SOM and keystone taxa (Schizothecium1), and keystone taxa were significantly driven by soil pH. This study suggested that rotation cropping might contribute to the improvement of soil ecosystem multifunctionality as well as the development of disease-suppressive soils, and provide theoretical basis for prevention and control of continuous cropping obstacles in potatoes.